A high-performance flexible direct ethanol fuel cell with drop-and-play function. (November 2019) - Wang, Jiaqi; Pei, Zengxia; Liu, Jie; Hu, Mengmeng; Feng, Yuping; Wang, Panpan; Wang, Hua; Nie, Ningyuan; Wang, Yueyang; Zhi, Chunyi; Huang, Yan
Abstract: Highly flexible direct ethanol fuel cells (DEFC) are a promising next frontier of energy conversion devices that will change the pattern of current flexible electronics. However, the major difficulties such as ethanol-crossover-induced catalyst poisoning and harsh conditions, limit the development of such devices. Here, we report for the first time a flexible drop-and-play DEFC that addresses all these difficulties via using a highly active oxygen reduction reaction (ORR) electrocatalyst which cannot be poisoned by ethanol, together with a superior alkali-compatible and ion-conductive hydrogel electrolyte. The fabricated flexible DEFC shows high performances of 21.48 mW cm −2 power density and 1.41 mWh cm −2 energy density at room temperature and atmospheric pressure. Moreover, it possesses excellent flexibility and unique drop-and-play function, easily powering an electronic clock and a smart phone. Such high-performance flexible DEFC with drop-and-play function opens up many new opportunities for next-generation flexible electronics. Graphical abstract: We report for the first time a flexible drop-and-play direct ethanol fuel cell (DEFC) using a highly catalytic oxygen reduction reaction electrocatalyst which cannot be poisoned by ethanol, as well as a superior alkali-compatible and ion-conductive hydrogel electrolyte membrane. The fabricated DEFC delivers a high energy density of 1.41 mWh cm −2 at room temperature and atmospheric pressure. Moreover, it possesses excellent flexibility and unique drop-and-play function. Image 1 Highlights: Porous NSDC ORR catalyst possessing anti-ethanol poisoning, high catalytic activity and one-step process. Hydrogel electrolyte with merits of superior ionic conductivity, long-time stability and high compatibility with alkali. High-performance flexible direct ethanol fuel cell with drop-and-play function.